Women’s Career in Media Industry of Pakistan: An Analysis of Patriarchy and Neo-Liberalism - Nabiha Fatima Shahram; Ahmad, Dr. Khalil (Journal of Peace, Development and Communication, 2023)
The present study attempted to understand the career trajectory of women employed in the Pakistani media houses. It proposed to understand womanity as a capital in the habitus of media industry, the influence of patriarchy and neo-liberalism. Qualitative research approach was used to evaluate the career of women in the media industry. Total (N=21) female employees working in different media houses, age group (25-60) full time registered employees were selected, research participants were selected from the registered media houses with All Pakistan Newspaper Society Purposive sampling technique was applied to conduct in-depth interviews, two focus group discussions were held. The hurdles women employee face due to ‘being a women’ in the media industry. The findings of the study showed that work experiences, success and career persuasion in the media industry were affected by numerous aspects including inter-sectionalizing of gender and social class, gendered genre of journalism. This study is helpful in making further recommendations for policy making, identifying the factors widening gender gaps and understanding the impact of social construction of gendered disparity resulting in further glass ceilings and barriers. The findings of the study gave an insight of the apartheid women face in the media and will provide a deep understanding of road blocks for women who form half of the population of Pakistan.